Environmentally Based Hospitality Management Assistance and Community Participation in the Kamasan Klungkung Tourism Village by Maintaining Local Wisdom - Latif, B Syarifuddin; Awaloedin, Dipa Teruna; Demolingo, Ramang H; Christiani, Meiliana (CV ODIS, 2024)
This Community Service activity aims to train the people of Kamasan Tourism Village about hospitality management, including managing natural resources as a potential business through Sapta Pesona. This training needs to be carried out because there is a need for services that have good and correct standards. It is hoped that village residents can develop their potential in welcoming tourists. The Tourism Study Program, Faculty of Economics and Business, National University, as a tourism managerial institution and an institution that organizes research activities, has a moral obligation to provide guidance. Community service program to provide hospitality management training and develop aspects of managing tourism villages and homestays properly and correctly. The next activity is Balinese food processing entrepreneurship, which includes training and practice. The next material is about persuasive text and describing a place, which explains how to use English or French properly and correctly. It is hoped that village residents can develop their potential to speak English or French to welcome foreign tourists. The final material is to provide Balinese dance training to children in tourist villages. The objectives of this training are: (1) To provide understanding and motivation about the importance of culture as national identity. (2) Transferring knowledge about Balinese art, both theory and practice. (3) Develop participants' creativity and self-confidence. (4) Provide insight into Indonesian Tourism, especially Bali